Sistem Informasi Penjualan Ikan Hias Pada Kios WNC Parung Berbasis Android - Tedi Purwanto; Simon Simarmata; Jamaludin (CV. Multi Kreasi Media, 2025)
Technological advancement has made various services increasingly fast, convenient, and accessible across different locations. Android, as one of the most widely used mobile operating systems, has become an attractive and highly sought-after platform for developing Android-based mobile applications. Therefore, our research aims to develop an information system for ornamental fish sales, specifically for WNC stand, based on the Android platform. The Android-based ornamental fish sales information system at WNC stand utilizes the waterfall methodology to assist stand managers in the sales process and promotion of ornamental fish. This system is expected to facilitate both sellers and consumers in resolving transaction-related issues with ease. The Android-based fish sales application is anticipated to benefit both sellers and consumers, as customers no longer need to visit traditional markets since they can view information, make purchases, and check fish availability using their smartphones. This research focuses on analyzing and solving social and real-life problems by implementing the waterfall methodology. The data collection techniques employed include observation and interviews, with this study being qualitative in nature. The expected outcome of this research is an Android-based ornamental fish sales information system application for WNC stand that facilitates user transactions in ornamental fish sales.